Pengaruh Experiental Marketing Dan Kepercayaan Terhadap Loyalitas Konsumen Pengguna Grab Food Di Kota Bima - Muhammad Fitrah Yusham; Intisari Haryanti; Ita Purnama (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence of experiential marketing and trust on consumer loyalty of Grab Food users in Bima City. This type of research is associative. The research instrument uses a Likert scale questionnaire. The population used is all Grab Food users who have purchased or ordered products from Grab Food. The sample in this study was 96 Grab Food users in Bima City. The sampling technique used is proportional sampling. Data collection techniques in this research are observation, questionnaires and literature study. Data analysis techniques use validity tests, reliability tests, classical assumption tests, multiple regression, multiple correlation coefficients, t tests and f tests. The research results show that experiential marketing and trust together have a significant effect on consumer loyalty of Grab Food users in Bima City.